-4x+6=0.5(x+36)

Simple and best practice solution for -4x+6=0.5(x+36) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x+6=0.5(x+36) equation:


Simplifying
-4x + 6 = 0.5(x + 36)

Reorder the terms:
6 + -4x = 0.5(x + 36)

Reorder the terms:
6 + -4x = 0.5(36 + x)
6 + -4x = (36 * 0.5 + x * 0.5)
6 + -4x = (18 + 0.5x)

Solving
6 + -4x = 18 + 0.5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.5x' to each side of the equation.
6 + -4x + -0.5x = 18 + 0.5x + -0.5x

Combine like terms: -4x + -0.5x = -4.5x
6 + -4.5x = 18 + 0.5x + -0.5x

Combine like terms: 0.5x + -0.5x = 0.0
6 + -4.5x = 18 + 0.0
6 + -4.5x = 18

Add '-6' to each side of the equation.
6 + -6 + -4.5x = 18 + -6

Combine like terms: 6 + -6 = 0
0 + -4.5x = 18 + -6
-4.5x = 18 + -6

Combine like terms: 18 + -6 = 12
-4.5x = 12

Divide each side by '-4.5'.
x = -2.666666667

Simplifying
x = -2.666666667

See similar equations:

| 402x-1.4y=2.1 | | (x^2)+3x=308 | | 2(d-4)=2d+8 | | 448x+8=448+x^2 | | -18=2y-8 | | 4x-22=2x-2 | | 448x+8=448 | | (x^2)+8x=308 | | 10=-3p+5 | | 16x-184=6x-14 | | 448x+8=11 | | 12x-4=3x+23 | | 79-4x=14x+17 | | 1.5+0.75a=0.25a-0.5 | | 11+2y=3.50 | | 3xx+2x-4=0 | | -6y+2=-13 | | 8+3a=1a | | h+-50=400 | | 5x+3(2x-8)=2(x+6) | | X^2+28x+49=0 | | 3xx+2x=0 | | -0.5(x-6)=20 | | 15n^2-26n-21=0 | | x=2x-6 | | 7x+12=-10-22 | | 7x+3=21x+9 | | 250+79.95t=1049.50 | | 7v^2+6v-1=0 | | 11.3-p/3.8=1.5 | | 4+3j=-8 | | -1x+2x+4-2= |

Equations solver categories